Ecology and plankton diversity of Bhara Haripota bhery, East Kolkata wetland, West Bengal - Kumar, Avinash; Das, S K; Bhakta, D (Journal of the Inland Fisheries Society of India, 2021)
Ecology and plankton diversity of Bhara Haripota Bhery, East Kolkata wetland was studied to find out the productivity status of the wetland. The range of water quality parameters of water were: temperature 18.7 -31.3 o C, transparency 19.2-25.8 cm, pH 6.85-7.91, DO 3.55-5.23 mg l-1, free CO2 2-12 mg l-1, total alkalinity 312-156 mg l-1, PO4 -P 0.18-1.26 mg l-1 and specific conductivity 540-1,676 Î¼S cm-1. Seasonal abundance of phytoplankton was highest in March with 3,567 ind l-1 and minimum during in August with 1,962 ind l-1. A total of 19 genera of phytoplankton were identified consisting of 6 genera of Chlorophyceae, 5 genera of Cyanophyceae, 4 genera of Bacillariophyceae, and 4 genera of Flagellates with Chlorophyceae being rich in species diversity. Some of the encountered dominant genera were Volvox, Ankistrosdesmus, Closterium, Euglena, Phacus, and Chlamydomonas. Shannon’s diversity indexes were recorded as 1.716, 1.49, 1.356, and 1.959 for Chlorophyceae, Cyanophyceae, Bacillariophyceae, and Flagellates respectively. In case of the Zooplankton population, the maximum (604 ind l-1) number was found during the post-monsoon season compared to other seasons. A total of 12 genera of zooplanktons were encountered comprising 3 of Protozoa, 3 of Rotifera, 3 of Copepoda, and 3 of Cladocera. The dominant species were Brachionus, Cyclops, Diaptomus, Daphnia, and Moina. Shannon’s index for Rotifers, Copepoda, Cladocera, and Protozoa were 0.9764, 1.069, 0.8838, and 0.9626 respectively. The study indicated that the wetland is moderately productive in aspects of plankton diversity and suitable for aquaculture. Key words Ecology; plankton diversity; East Kolkata wetland